Pharmacological management of maternal hypertension during breastfeeding: A therapeutic challenge - Tutal Muñoz, Luis Miguel (2019)
Introduction: Hypertensive disorders of pregnancy may persist or appear in the postnatal period, and may require treatment while breastfeeding. There is no current consensus on the pharmacological management of hypertension in this context, and it may represent a challenge for the clinician. Objective: To review the literature on the pharmacological management of maternal hypertension during breastfeeding. Methods: We conducted a literature search on the subject in ScienceDirect, PubMed-Medline, Embase biomedical, SciELO and Cochrane Library, using the terms: “pregnancy induced hypertension AND therapeutics”, “postpartum hypertension AND therapeutics”, “pregnancy induced hypertension AND treatment”, “postpartum hypertension AND treatment”. Results: Forty-four relevant articles were considered suitable for this review. Conclusions: The literature reviewed suggests that nifedipine, enalapril, captopril and metoprolol are relatively safe drugs for the breastfeeding infant.